Murujuga Rockshelter: First evidence for Pleistocene occupation on the Burrup Peninsula. (1st August 2018) - McDonald, Jo; Reynen, Wendy; Ditchfield, Kane; Dortch, Joe; Leopold, Matthias; Stephenson, Birgitta; Whitley, Tom; Ward, Ingrid; Veth, Peter
Abstract: The Dampier Archipelago (including the Burrup Peninsula), now generally known as Murujuga, is a significant rock art province in north-western Australia which documents the transition of an arid-maritime cultural landscape through time. This archipelago of 42 islands has only existed since the mid-Holocene, when the sea level rose to its current height. Previous excavations across Murujuga have demonstrated Holocene occupation sequences, but the highly weathered rock art depicting extinct fauna and early styles suggests a far greater age for occupation and rock art production. The archaeological record from the Pilbara and Carnarvon bioregions demonstrates human occupation through 50, 000 years of environmental change. While the regional prehistory and engraved art suggests that people were producing art here since they first occupied these arid rocky slopes, no clear evidence of Pleistocene occupation has been found across Murujuga, until now. Murujuga Rockshelter (MR1) reveals that occupation of this shelter began late in the Last Glacial Maximum, when the Murujuga Ranges would likely have served as one of a network of Pilbara refugia. In the terminal Pleistocene/Early Holocene, and likely in tandem with the last stages of sea level rise, the proportion of artefacts manufactured on exotic lithologies declines sharply, revealing a changed foraging range and increasing territorial focus in this period of increased demographic packing as the coastline advanced. Abandonment of the site as early as 7000 years ago is indicated, suggesting a changing resource focus to the increasingly proximal coastline. This paper provides the first evidence of how Aboriginal people adapted their Pleistocene procurement strategies in response to significant environmental and landscape changes in Murujuga. This changing logistical strategy provides an explanation for the increased rock art production in the terminal Pleistocene/Early Holocene. Highlights: We demonstrate Pleistocene occupation at the world's largest rock art complex. Bayesian, stratigraphic, sedimentological and artefact analyses place first human occupation at 21 ka with repeated occupations until c.7 ka. Site abandonment is interpreted as restructuring of settlement on Murujuga towards the newly arriving coast.